Gambaran De Quervain Syndrome Akibat Penggunaan Gadget Pada Siswa Madrasah Tsanawiyah Al-Mawahib - Nafi'ah Nafi'ah; Raudatul Jannah; Dian Intan Permatasari (UPPM Politeknik Unggulan Kalimantan, 2023)
De Quervain Syndrome arises due to inflammation of the Extensor Pollicis Brevis tendon and the Musculus Abductor Pollicis Longus tendon caused by trauma or excessive loading. Objective: To find out the description of De Quervain Syndrome due to the use of gadgets in students of Madrasah Tsanawiyah Al-Mawahib. Benefits: This study can increase knowledge about the description of De Quervain Syndrome due to the use of gadgets by doing the Finkelstein test. Research Methods: This research was conducted at Madrasah Tsanawiyah Al-Mawahib by filling out a form and doing a Finkelstein test. Conclusion: From the research conducted, it was found that respondents who used gadgets with a percentage of 100%, based on duration, more results were obtained <6 hours with a percentage of 66%, based on De Quervain Syndrome because gadgets obtained overall more negative results with De Quervain Syndrome with a percentage of 53 %, positive for De Quervain Syndrome due to gadgets based on gender, the results are more women than men with a percentage of 7%, positive for De Quervain Syndrome due to gadgets based on age, 14 year olds have more De Quervain Syndrome with a percentage of 6%.